Immigrant Students at School in Spain: Constructing a Subject of Study - Francisco Javier García Castaño; Maria Rubio Gomez; Ouafaa Bouachra (Dve domovini (Tiskana izd.), 2015)
This article discusses the various contexts of the public education of immigrant students in Spain, bringing together the relevant body of literature from more than ten years of research. It provides a description of the distribution of immigrant students at the national and local level, elucidating an analysis of the perception and management of immigrant students within the Spanish education system, presenting the different types of classroom assistance provided for these students and the pivotal role of language management in school. The article concludes by presenting critical approaches to the problems discussed.